NlCYP4G76 and NlCYP4G115 Modulate Susceptibility to Desiccation and Insecticide Penetration Through Affecting Cuticular Hydrocarbon Biosynthesis in Nilaparvata lugens (Hemiptera: Delphacidae) - Wang, Shengyin; Li, Baoling; Zhang, Dayu (Frontiers in Physiology, 2019)
The functions of cuticular hydrocarbons (CHCs) are varied in insects, and one of them is to reduce water loss. Previous work has concluded that biosynthesis of cuticular hydrocarbons are strongly related to the CYP4G sub-family. Targeting these genes in the brown planthopper, Nilaparvata lugens Stål, might be a new application for integrated pest management. Therefore, we explored the functions of CYP4G76 (GenBank: KM217045.1) and CYP4G115 (GenBank: KM217046.1) genes in this study. The desiccation treatment (RH < 5%) for duration of 1-3 d significantly increased the transcription level of CYP4G76 and CYP4G115. RNAi through the injection of CYP4G76 and CYP4G115 dsRNA could significantly decrease their expression, respectively, and further reduced the biosynthesis of CHCs, i.e. saturated and straight-chain alkanes. When CYP4G76 and CYP4G115 were suppressed, the susceptibility of N. lugens nymphs to desiccation increased, due to the deficiency of the CHCs in the insect’s cuticle. When the expression of CYP4G76 and CYP4G115 was decreased, this resulted in an increased rate of penetration of the four insecticides: pymetrozine, imidacloprid, thiamethoxam, and buprofezin. This was especially the case for thiamethoxam. Therefore, CYP4G76 and CYP4G115 appear to regulate the biosynthesis of CHCs in N. lugens nymphs, which play a major role in protecting insects from water loss and the penetration rate of insecticides. CYP4G76 and CYP4G115 might be used as a novel target in integrated pest management to N. lugens.